Rett Syndrome: A Case report - Shrestha, M; Rajbhandari, A (Journal of Nepal Paediatric Society, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Rett syndrome (RS) is a severe neuro-developmental disorder leading to severe intellectual disability in females all around the world. A four-year-old girl from Kathmandu presented with classic features of Rett syndrome (RS), including developmental regression with dementia, loss of acquired speech and hand function, and stereotypic hand movements along with generalized tonic clonic convulsion. Key words: Rett Syndrome, Developmental Regression DOI = 10.3126/jnps.v28i1.1401 J. Nepal Paediatr. Soc. Vol.28(1) p.17-19